ِTHE MORPHOLOGICAL AND HISTOLOGICAL STUDY OF THE CAECUM IN BROILER CHICKEN - M. F. Majeed; F.S. Al- Asadi; A. N. Al. Nassir; E. H.Rahi (Basrah Journal of Veterinary Research)
Morphological and histological study were performed in the cecum of ten, six months broiler chicken. The present study was observed that the morphological study distinguished three region from cecum .The proximal ,middle ,and distal represented (23.65%),(42.28%),(34.06%) respectively of the total length of right caecum ,and (23.59%),(43.45%),(23.95%) respectively of the total length of left caecum.The total length of the right caecum were(13.15±0.21)while the total length of left caecum were(13.14±0.44),also was observed that caecal wall composed of four layers( mucosa , submucosa , muscularis and serosa) .The regions of caecum were proximal with developed villi and numerous folds, middle with small villi and numerous folds,while the distal with small villi and avoid of folds .In present study the lymphatic nodules were mostly found in proximal part, but they were less prominent at the distal and least in the middle part of the caecum .the wide and length of lymphatic nodules were more major in the distal part than in the middle and proximal part